Quantifying "quantitative tightening" (QT): How many rate hikes is QT equivalent to? - Bin Wei (Federal Reserve Bank of Atlanta, 2022)
How many interest rate hikes is quantitative tightening (QT) equivalent to? In this paper, I examine this question based on the preferred-habitat model in Vayanos and Vila (2021). I define the equivalence between rate hikes and QT such that they both have the same impact on the 10-year yield. Based on the model calibrated to fit the nominal Treasury data between 1999 and 2022, I show that a passive roll-off of 2.2 trillion over three years is equivalent to an increase of 29 basis points in the current federal funds rate at normal times. However, during a crisis period with risk aversion being doubled, it is equivalent to a 74 basis point increase. I also quantify the effect of QT implemented by active sales. Lastly, based on the model-based estimates, I show that if the Treasury were to issue bills to offset maturing securities, the resulting equivalent rate hikes in the current federal funds rate would decrease dramatically to 7.4 (12.6) basis points during normal (crisis) periods.
Keywords: E43; E44; E52; E58; G12; 330; monetary policy; quantitative tightening; QT; quantitative easing; QE; rate hikes; preferredhabitat; reserves; reverse repo